Analysis of the Effect of Product Quality and Service Quality on Customer Loyalty Mediated by Customer Satisfaction at Kafe Kudu, Jalan Sei Petani, Medan City (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of product quality and service quality on customer loyalty, with customer satisfaction serving as a mediating variable at Kafe Kudu, located on Jalan Sei Petani, Medan City. A quantitative approach was employed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The study involved a sample of 90 respondents selected through purposive sampling. The results indicate that product quality does not have a significant effect on customer satisfaction but has a significant impact on customer loyalty. Conversely, service quality significantly affects both customer satisfaction and customer loyalty. Furthermore, customer satisfaction significantly influences customer loyalty. The mediation test results show that customer satisfaction does not significantly mediate the relationship between product quality and customer loyalty but does significantly mediate the relationship between service quality and customer loyalty. These findings suggest that, within the context of Kafe Kudu, enhancing service quality is a more effective strategy for fostering customer satisfaction and loyalty than focusing solely on product quality. Therefore, it is recommended that management prioritize improving service quality as a long-term strategic initiative